ANALISIS PENGARUH PERSEPSI, KEPUASAN, DAN KETERIKATAN KARYAWAN TERHADAP EFEKTIVITAS PENERAPAN HUMAN RESOURCES INFORMATION SYSTEMDI PT KAWASAN BERIKAT NUSANTARA - Dewi Susanti; Anandha Budiantoro (CV. Denasya Smart Publisher, 2024)
PT Kawasan Berikat Nusantara (KBN) is a company that implements HRIS as a human resource management tool. However, the effectiveness of implementing HRIS can be influenced by several factors, such as employee perception, satisfaction and engagement with this system. Employee perceptions of HRIS are very important because they can influence the acceptance and use of this system. If employees have a positive perception of HRIS, they will be more accepting and use this system effectively. The research results show that employee perceptions have a direct positive effect on the effectiveness of implementing the Human Resources Information System (EP) with a path coefficient value of 0.646 or 64.6 percent. Apart from that, employee satisfaction also has a direct positive effect on the effectiveness of implementing the Human Resources Information System (EP) with a path coefficient value of 0.132 or 13.2 percent. And employee engagement has a direct positive effect on the effectiveness of implementing the Human Resources Information System (EP) with a path coefficient value of 0.099 or 9.9 percent.